2016
DOI: 10.18632/oncotarget.7834
|View full text |Cite
|
Sign up to set email alerts
|

CD226 ligation protects against EAE by promoting IL-10 expressionviaregulation of CD4+ T cell differentiation

Abstract: Treatment targeting CD226 can ameliorate experimental autoimmune encephalomyelitis (EAE), the widely accepted model of MS. However, the mechanisms still need to be elucidated. Here we showed that CD226 blockage by anti-CD226 blocking mAb LeoA1 efficiently promoted IL-10 production in human peripheral blood monocytes (PBMC) or in mixed lymphocyte culture (MLC) system, significantly induced the CD4+IL-10+ T cell differentiation while suppressing the generation of Th1 and Th17. Furthermore, CD226 pAb administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Several lines of evidence have demonstrated that CD226 plays a crucial role in the formation of immune synapses, and it is primarily considered to be an active receptor of NK and T cells ( 3 , 39 ). The results of our previous studies demonstrated that mice treated with an anti-CD226 pAb in vivo have markedly decreased EAE susceptibility ( 27 ), in agreement with recent data showing that CD226 is involved in the pathogenesis of autoimmune diseases ( 8 , 9 ). EAE is caused by the breakdown of self-tolerance and eventually leads to myelin-reactive CD4 + T cell infiltration of the CNS to mediate neuronal inflammation ( 11 , 29 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several lines of evidence have demonstrated that CD226 plays a crucial role in the formation of immune synapses, and it is primarily considered to be an active receptor of NK and T cells ( 3 , 39 ). The results of our previous studies demonstrated that mice treated with an anti-CD226 pAb in vivo have markedly decreased EAE susceptibility ( 27 ), in agreement with recent data showing that CD226 is involved in the pathogenesis of autoimmune diseases ( 8 , 9 ). EAE is caused by the breakdown of self-tolerance and eventually leads to myelin-reactive CD4 + T cell infiltration of the CNS to mediate neuronal inflammation ( 11 , 29 ).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Cd226 −/− mice tended to show reduced weight loss (days 4-6 and 20-28 after MOG 35−55 immunization), a feature associated with EAE progression (26), although this effect was not significant (Supplemental Figure 2A). These data collectively indicated that CD226 deficiency in EAE mice may alleviate the severity of inflammation, which is consistent with previous studies showing that mice treated with an anti-CD226 polyclonal antibody (pAb) in vivo were resistant to EAE development and progression (27).…”
Section: Cd226 -/-Mice Are Less Susceptible To Eae and Lower Levels Osupporting
confidence: 92%
“…Experimental autoimmune encephalomyelitis (EAE) contributes to a breakdown of self-tolerance and leads to Th17 cells infiltrating the central nervous system to mediate inflammation and neuronal injury ( Rostami and Ciric, 2013 ). Zhang et al reported that EAE susceptibility in mice treated with anti-CD226 pAb was markedly decreased via balancing the Th17/Treg ratio ( Rong et al, 2016 ), and the enhanced suppressive capacity of Tregs during EAE is related to the absence of CD226 and the increased expression levels of TIGIT ( Ning et al, 2019 ). Ulcerative colitis (UC) is a chronic inflammatory immune-related disease.…”
Section: Cd226 and Clinical Diseasesmentioning
confidence: 99%
“…More importantly, inhibition of Th17 cell differentiation could significantly ameliorated MOG (35-55)-induced EAE [ 18 , 19 ]. For example, CD226 pAb administration was found to reduced onset of EAE by inhibiting Th1/Th17 production [ 20 ]. Furthermore, huma truncate IL12rβ1-Fc fusion protein could ameliorate EAE and suppress demyelination in CNS by reducing production of Th1 and Th17-polarized proinflammatory cytokines [ 21 ].…”
Section: Discussionmentioning
confidence: 99%